Concept of Sin and its Punishment in the Holy Quran and Sunnah, Research and Analytical Study in the Light of Surah Fatir Verse No. 18 - Dr. Aftab Ahmad,; Dr. Amin Ullah,; Dr. Rasheed Ahmed,; Dr. Navid Iqbal*, (Al-Qanṭara, 2023)
Allah has created humans for His worship and has created both good and evil substances in human nature. Along with this, man has also been given the right to choose whatever path he wants to take. Now, if he takes the path of goodness, then rewards and rewards have been set for him, and if he takes the path of evil, then sins and punishment have been set for him. The perspective of Quran and Sunnah regarding reward and sin is also very clear. Therefore, whoever commits a sin will be punished for it, similarly whoever does good deeds will also be rewarded for it. Allah has made a clear law that everyone will bear the burden of their sins, and everyone will be held accountable for their actions. Therefore, no person will be held accountable for the sins and crimes of another person. Therefore, some scholars say that adultery is a debt, it will be repaid by the family of the person committing adultery. This is a claim that seems to be against the Qur'an and Sunnah. Therefore, in this paper, an analytical study will be done about sin and its punishment in the light of the Holy Quran and hadiths, so that it can be known what the concept of the Quran and Sunnah is about sin and its punishment. Keywords; Sin & punishment, Quran & Sunnah, Analytical Study, Surah Fatir